INFLUENCE OF ENERGY DRINKS ON THE MORPHOLOGICAL STRUCTURE OF THE UTERUS (E Global Congress, 2024)
To develop a detailed understanding of the effects of regular consumption of energy drinks on the morphological aspects of the uterus in women, including an assessment of changes in tissue, structure and functional activity of the organ. Specifically, the study aims to identify possible abnormalities, degenerative changes or other pathological processes that may be associated with the consumption of energy drinks, with the goal of providing specific data for the development of recommendations for the safe use of such drinks and the protection of women's health.